Pholedrine: a substitute for hydroxyamphetamine as a diagnostic eyedrop test in Horner's syndrome. Issue 2 (February 1995) - Bates, A T; Chamberlain, S; Champion, M; Foley, L; Hughes, E; Jani, B; Mehta, H; Smith, S E
Abstract : Mydriatic responses to eyedrops containing the indirect acting sympathomimetic amines tyramine, hydroxyamphetamine, and pholedrine have been compared in 10 healthy subjects. Pholedrine, the n-methyl derivative of hydroxyamphetamine, at a concentration of 1% had effects similar to those produced by 0.5% hydroxyamphetamine itself. Pretreatment with topical guanethidine attenuated its responses and in 13 patients with unilateral Horner's syndrome it distinguished clearly those five patients who had preganglionic from the eight with postganglionic lesions. It is concluded that 1% pholedrine may be substituted for 0.5% hydroxyamphetamine, which is no longer available, as a diagnostic agent for use in Horner's syndrome.